Chemical, functional and sensorial evaluation of the low cholesterol dehydrated egg yolk - Borges, Soraia Vilela (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this work was to evaluate the effect of extration, with acetone, of egg yolk cholesterol on yolk lipidic composition and adequacy as ingredient in the mayonnaise preparation. The extraction was proceeded under previously optimized conditions. The lipidic composition of the raw material and extract phase was determined and, by mass balance, the lipidic composition of the final product was estimated. The emulsion stability and sensorial analysis of two mayonnaise's formulations were carried out for low cholesterol egg yolk. Results showed that the acetone reduced 30% of the total lipids and 81% of the cholesterol and increased 42% of the phospholipids. The stability of mayonnaise emulsion was not significantly different when compared to that obtained with the egg yolk control (without cholesterol extraction). The sensorial tests showed that the product was considered acceptable by about 55% of the judges. The overall results indicate that the extraction with acetone is a promising technology for obtaining low cholesterol egg yolk.
Keywords: chemical composition; functional property; cholesterol extraction